Implementation the Analysis of Hazard Analysis and Critical Control Points (HACCP) for Aljaya’s Martabak at Rungkut Madya, Surabaya - Erwan Adi Saputro; AR Yelvia Sunarti; Ika Nawang Puspitawati; Tiffanie Dewi Arifilla; Febry Widiatniko Handy (Nusantara Science and Technology Proceedings, 2023)
In Indonesia, the martabak food culture is modified into two forms, namely sweet martabak and egg martabak. Sweet martabak has a thicker texture than egg martabak. Martabak Aljaya's at Rungkut madya has a menu variant, namely egg martabak. Egg martabak is a culinary food made from eggs, wheat flour, ground beef with a combination of spices such as shallots and white onions, chilies, pepper, spring onions, and oil for sautéing. Egg martabak is a food that is processed by frying. The characteristics of the egg martabak are that it has a savory, salty and chewy taste. The egg martabak is packaged in a food box and topped with some green chilies and can be distributed directly to buyers/customers who will buy the product or delivered by vehicle on party orders (orders in large quantities) and provide recommendations to Analyzing Hazard and Critical Control Point (HACCP) on the Aljaya's egg martabak menu at Rungkut Madya, Surabaya.